2021
DOI: 10.21203/rs.3.rs-748301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Removal of phenol from aqueous solution using biochar produced from Araucaria Columnaris Bark

Abstract: This work investigates the removal of phenol from aqueous solution using Araucaria Columnaris bark (ACB) as biochar. Five different types of biochars were developed through pyrolysis at different temp from 300 to 500°C. The effects of initial concentration, contact time, pH and temperature on adsorption behavior were studied in batch mode for each biochar. The optimum contact time observed for equilibrium condition was 60 mins for every biochar. And, the maximum adsorption followed the order 298 K > 308 K &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The important parameters such as heat treatment time and temperature should be optimized for the synthesis of highly efficient biochar. Adsorption capacity is directly related to the porosity of biochar (Chandola et al, 2021; Wang & Wang, 2019). Several studies have been reported on the analysis of the adsorption efficiency of plant waste biochar on phenol adsorption (Acharya et al, 2018; Afsharnia et al, 2016; Chandola et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important parameters such as heat treatment time and temperature should be optimized for the synthesis of highly efficient biochar. Adsorption capacity is directly related to the porosity of biochar (Chandola et al, 2021; Wang & Wang, 2019). Several studies have been reported on the analysis of the adsorption efficiency of plant waste biochar on phenol adsorption (Acharya et al, 2018; Afsharnia et al, 2016; Chandola et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption capacity is directly related to the porosity of biochar (Chandola et al, 2021; Wang & Wang, 2019). Several studies have been reported on the analysis of the adsorption efficiency of plant waste biochar on phenol adsorption (Acharya et al, 2018; Afsharnia et al, 2016; Chandola et al, 2021). For the plant waste adsorbent, orange peel biochars show a high adsorption capacity for the removal of heavy metals (Tran et al, 2016), dye (Amin et al, 2019; Kapoor & Sivamani, 2023), and organic impurities like phenols (Ikpe et al, 2017; Rana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%